2004
DOI: 10.1590/s0103-90162004000300013
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and pH of the nutrient solution on wheat primary root growth

Abstract: Primary root growth is very important for wheat (Triticum aestivum L.) crop in upland conditions in the State of São Paulo. Fourteen wheat genotypes (mutant lines and cultivars) were evaluated for primary root growth during 7 and 15 days of development in complete and aerated nutrient solutions, in the laboratory. In the first experiment, solutions with three pH values (4.0, 5.0 and 6.0) at constant temperature (24 ± 1°C), and in the second experiment, solutions with the same pH (4.0) but with three temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
1
3
0
2
Order By: Relevance
“…Wheat is one of the first domesticated species to man and is also the first agricultural product used in food processing showing fundamental role in the human food base (Silva et al 2014). The wheat grain has important role in the economic and nutritional aspects of food because their flour is widely used in food industry for the production of flour especially in bread and pasta (Camargo et al 2004). Sprouting grains for human consumption has been used for centuries in Egypt and Asian counties to improve food value (Resh, 2001 andAbdallah, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Wheat is one of the first domesticated species to man and is also the first agricultural product used in food processing showing fundamental role in the human food base (Silva et al 2014). The wheat grain has important role in the economic and nutritional aspects of food because their flour is widely used in food industry for the production of flour especially in bread and pasta (Camargo et al 2004). Sprouting grains for human consumption has been used for centuries in Egypt and Asian counties to improve food value (Resh, 2001 andAbdallah, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Por ser uma cultura predominantemente de inverno, o trigo é mais cultivado na região sul do Brasil, principalmente nos Estados do Paraná e do Rio Grande do Sul, embora também seja cultivado em outros estados como São Paulo, Minas Gerais e Mato Grosso do Sul. Muitas vezes, o trigo é utilizado como cultura de rotação, principalmente com a soja, devido ao fato da soja ser uma cultura de verão e o trigo uma cultura de inverno (CAMARGO; FERREIRA-FILHO;SALOMON, 2004).…”
Section: Introductionunclassified
“…Paralelamente, tem ocorrido uma maior importação de trigo por esses países, já que a sua produção interna não atende a demanda de consumo (CAMARGO; FERREIRA-FILHO; SALOMON, 2004;MIRANDA, 2002). Devido ao fato do Brasil não ser auto-suficiente no abastecimento de trigo, o país necessita de trigo importado para atender às suas necessidades internas.…”
Section: Introductionunclassified
“…When grown in sand, L. angustifolius develops shorter and a higher proportion of thick roots in pH 7.5 [51]. Another study using pH 4-6 found that genotypic differences among wheat lines are larger than root growth difference in different pH levels [52]. Contrastingly, soil-grown durum wheat roots were shown to increase their rhizosphere pH to ~8.0 [42].…”
Section: P-form Complexity Within Algae Biomass Offers Potential For ...mentioning
confidence: 98%